An analysis of value system of taekwondo freestyle poomsae`s trainees: based on means-end chain theory and apt laddering technique - Choi, Y. L.; Park, J. C.; Kim, I. G. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction Today, Taekwondo gyms are experiencing a continuous decrease in the number of trainees, due to the oversupply of the gyms, excessive competition, and the COVID-19 pendemic. To solve the problems, various programmes are needed to satisfy the needs of Taekwondo trainees. Among them, Freestyle Poomsae allows trainees to feel more fun, artistry, and creativity than other Taekwondo events. In this context, it is necessary to study what kind of decision-making process trainees start and continue the Freestyle Poomsae. Therefore, the purpose of this study is to explore the attributes, benefits and values of Freestyle Poomsae perceived by trainees, and then to understand the connection relationship and cognitive process based on a Means-End Chain method proposed by Gutman(1982).